A step toward healthy newborn: An assessment of 2 years' admission pattern and treatment outcomes of neonates admitted in special newborn care units of Gujarat - Harsh Dilipkumar Shah; Bonny Shah; Paresh V Dave; Janak B Katariya; Khyati P Vats (Wolters Kluwer Medknow Publications, 2018)
Context: Facility Based Newborn Care (FBNC) is a key strategy to improve child survival, especially in newborn care where neonatal mortality rate (NMR) is stagnant in declining. Gujarat has achieved considerable amount of reduction in child deaths, but neonatal health requires attention. The study was aimed to assess the admission pattern of Special Newborn Care Units (SNCUs) which supports decision-making. Settings and Design: A cross-sectional descriptive analysis was done from secondary data of the SNCU reports on the aspects of admission patterns, morbidity, and mortality pattern. The reports had been analyzed on various critical variables. Results: In 2015-2016, Gujarat has operationalized forty SNCUs by saturating each district with at least one SNCU. The study found near proportions of (53%) inborn - (47%) outborn admission and 44% admission of female. Out of 69,662 admissions, 67% were discharged, 16% died, 10% leaving against medical advice, and 7% referred to higher centers. Major reasons for admission were respiratory distress syndrome (RDS) (22%) and infection (21%). Similar pattern in mortality found as final diagnosis of deaths was RDS (23%) and infection (21%). The proportion of neonatal deaths in outborn was high compared to inborn. Conclusion: Strengthening of FBNC is essential to address neonatal mortality. NMR is of prime focus because the health interventions needed to tackle NMR differ from those needed for infant mortality rate and under-five mortality rate. This accentuates the need for focused attention on facility- and community-based child health interventions along with quality maternal health services and robust referral mechanisms to all delivery points.